1992
DOI: 10.1148/radiology.184.2.1620852
|View full text |Cite
|
Sign up to set email alerts
|

Stenosis of the renal artery: assessment of slowed systole in the downstream circulation with Doppler sonography.

Abstract: Slowing and dampening of systole in the arterial network distal to stenosis is a well-known Doppler sign of severe arterial stenosis. To determine whether this sign is present in boys and girls with such stenosis, intrarenal Doppler curves (acceleration index [AI] and resistive index [RI]) were compared with findings on renal arteriograms in 20 boys and girls; the AI was also measured in 10 boys and girls without renal disease. Statistical analysis of AI and RI measurements was performed. Eleven of 32 renal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 0 publications
0
37
2
Order By: Relevance
“…On the other hand, in a comprehensive review, the authors [19,34] found for AT and AI a sensitivity of 80% and 74% and a specificity of 88% and 85%, respectively. Many factors influence systolic acceleration and may make the test nonspecific.…”
Section: Distal Criteria (Indirect Evaluation Of the Stenosis)mentioning
confidence: 99%
“…On the other hand, in a comprehensive review, the authors [19,34] found for AT and AI a sensitivity of 80% and 74% and a specificity of 88% and 85%, respectively. Many factors influence systolic acceleration and may make the test nonspecific.…”
Section: Distal Criteria (Indirect Evaluation Of the Stenosis)mentioning
confidence: 99%
“…To overcome this, some investigators have utilized so-called dampening of the waveform distal to a significant stenosis. A pressure drop across a stenosis is reflected distally by diminished systolic velocity and prolonged systolic acceleration time (3,7,8,12,13,20). The use of the Doppler technique in suspected renal transplant artery stenosis was first introduced by REINITZ et al (1 5).…”
Section: Discussionmentioning
confidence: 99%
“…The use of acceleration time (AT), acceleration index (AI) and RI have been reported earlier (9,12,20). STAVROS et al (20) used in addition a simple pattern recognition method, in which a loss of the early systolic compliance peak/reflective wave complex was the sign of a more than 60% stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first type manifested as a slowed rise to peak systolic velocity ('pulsus tardus phenomenon') and loss of the normally occurring early systolic velocity peak. [21][22][23][24] The second type was a lowering of the renal resistive index (peak systolic velocity/maximum end diastolic velocity). 25,26 These changes were shown to be result of a complex interaction between the resistance to flow and the compliance of the post-stenotic vessel wall.…”
Section: Ultrasoundmentioning
confidence: 99%